Examining the Effect of Electronic Information System’s Use on Time Management in Jordanian Banks - Md Faruk, Abdullah; Bunyamin Adewale, Bello; Mahmoud Saleem, Eial Awwad (2018)
The world is rapidly changing with new developments which have changed the manner, process or procedure of operations and activities in the business world. Electronic information system is one element that has introduced new trends in the way companies conduct their business activities especially in time management. However, whether this phenomenon has been examined in Arab world context is a question arising in the current dispensation due to limited literature existing. Thus, this study examined the effect of electronic information system on time management in Jordanian banks. Data were collected through questionnaires distributed to the employees in the banks in Jordan in which 452 were obtained back. Structural Equation Modelling was used to model the relationship between the variables using AMOS 24. The findings revealed that electronic information system has a positive direct effect on time management. This shows the readiness of the banking sector to keep abreast with the current trends in the market by adopting new processes for betterment of its services to the customer.